2020
DOI: 10.1080/1744666x.2020.1803064
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis and treatment of idiopathic and rheumatoid arthritis-related interstitial pneumonia. The possible lesson from COVID-19 pneumonia

Abstract: Introduction Main clinical manifestations of SARS-CoV-2 infection are characterized by fever, dyspnea, and interstitial pneumonia, frequently evolving in acute respiratory distress syndrome (ARDS). Areas covered Features of coronavirus disease 2019 (COVID-19) presents some common points with interstitial lung disease (ILD) both idiopathic and related to rheumatoid arthritis (RA), typically characterized by a chronic progression over time and possibly complicated by acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 111 publications
(169 reference statements)
0
5
0
2
Order By: Relevance
“…Germs such as Proteus spp. and Porphyromonas gingivalis are thought to be involved in the pathogenesis of RA-ILD [ 13 , 14 ].…”
Section: Pathogenesismentioning
confidence: 99%
“…Germs such as Proteus spp. and Porphyromonas gingivalis are thought to be involved in the pathogenesis of RA-ILD [ 13 , 14 ].…”
Section: Pathogenesismentioning
confidence: 99%
“…Some authors also suggest the inhibition of toll-like receptor 4 (TLR4) [48], which have been previously investigated as a possible therapeutic target for preventing lethal complications of some viral diseases [48]. The role of TLR4 in the pathogenesis of RA and RA-ILD has been demonstrated and its inhibition in experimental model showed to suppress the production of IL6, IL8, metalloproteinase-1 and vascular endothelial growth factor [49].…”
Section: Covid-19 Pneumonia and Ra-related Interstitial Lung Disease mentioning
confidence: 99%
“…Virus-induced lung injury, immune response, and attempts at healing are central to the process of fibrogenesis (Ojo et al, 2020). Features of COVID-19 presents some common points with IPF and RA-ILD, typically characterized by a chronic progression over time and possibly complicated by acute exacerbation (Manfredi et al, 2020). Our data showed that LTBP2 expression was up-regulated in patients with IPF, RA-ILD and COVID-19-related PF.…”
Section: Discussionmentioning
confidence: 61%